2022
DOI: 10.3390/nu14142868
|View full text |Cite
|
Sign up to set email alerts
|

Choline Supplementation Modifies the Effects of Developmental Alcohol Exposure on Immune Responses in Adult Rats

Abstract: Prenatal alcohol exposure can disrupt the development of numerous systems, including the immune system. Indeed, alterations in cytokine levels may contribute to the neuropathological, behavioral, and cognitive problems, and other adverse outcomes observed in individuals with fetal alcohol spectrum disorders. Importantly, supplementation with the essential nutrient choline can improve performance in hippocampal-dependent behaviors; thus, the present study examined the effects of choline on plasma and hippocampa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 85 publications
1
10
0
Order By: Relevance
“…Choline could also reprogram anti-inflammatory responses with the activation of INFg and TNFa [ 33 , 34 ] in females ( Figure 6 ). In this regard, there is evidence that prenatal choline supplementation mitigates fetal alcohol-exposure-induced pro-inflammatory responses in the adult rat hippocampus [ 35 ]. Thus, the role of prenatal choline in neuroinflammation deserves further analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Choline could also reprogram anti-inflammatory responses with the activation of INFg and TNFa [ 33 , 34 ] in females ( Figure 6 ). In this regard, there is evidence that prenatal choline supplementation mitigates fetal alcohol-exposure-induced pro-inflammatory responses in the adult rat hippocampus [ 35 ]. Thus, the role of prenatal choline in neuroinflammation deserves further analysis.…”
Section: Discussionmentioning
confidence: 99%
“…These neuroprotective effects are consistent with other studies that have shown that MCS lessens the adverse cognitive effects of various developmental insults, including models of various neurological disorders (e.g., Down syndrome. Alzheimer's disease, autism), toxicant exposure (e.g., alcohol), and other environmental influences (e.g., prenatal stress) 28,29,[94][95][96][97][98][99][30][31][32][33][90][91][92][93] . For example, MCS has been shown to lessen the functional deficits produced by developmental alcohol exposure in both rodent models 28,35,96,[98][99][100] , and humans 36,101 .…”
Section: Discussionmentioning
confidence: 99%
“…Alzheimer's disease, autism), toxicant exposure (e.g., alcohol), and other environmental influences (e.g., prenatal stress) 28,29,[94][95][96][97][98][99][30][31][32][33][90][91][92][93] . For example, MCS has been shown to lessen the functional deficits produced by developmental alcohol exposure in both rodent models 28,35,96,[98][99][100] , and humans 36,101 . And of particular interest to the present study, MCS has been shown to lessen the attentional dysfunction, as well as to normalize behavioral reactivity to committing an error or not receiving an expected reward in a mouse model of Down syndrome 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Choline could also reprogram anti-inflammatory responses with an activation of INFg and TNFa [33, 34] in females (Figure 6). In this regard, there is evidence that prenatal choline supplementation mitigates fetal alcohol-exposure induced pro-inflammatory responses in the adult rat hippocampus [35]. Thus, the role of prenatal choline supplementation in neuroinflammation deserves further analyses.…”
Section: Discussionmentioning
confidence: 99%